'Give us a break!': using a solution focused programme to help young people cope with loss and negative change. Issue 1 (2nd January 2018) - Whitehead, Lisa; Allan, Marie Clare; Allen, Kristen; Duchak, Valerie; King, Elizabeth; Mason, Corina; Mooney, Lindsay; Tully, Scott
Abstract: This research evaluated the impact of Give us a break! (GUAB!) — a programme for children and young people who have experienced bereavement or negative change including the impact of divorce/separation; experiences around ill health and circumstances leading to individuals being 'looked after'. A repeated measures design was utilised to measure the pre-post difference in the factors which contribute to young people's resilience following intervention. Additionally, as the programme is based on a model of Solution Focused Brief Therapy — which aims to develop a positive orientation towards the future — optimistic thinking was closely evaluated. Young people completed the Resiliency Scales for Children and Adolescents (Prince-Embury, 2006 ) and, to increase the rigour of data collection, parents/carers and teachers completed the Devereux Student Strengths Assessment (LeBuffe, Shapiro & Naglieri, 2009). The findings provide evidence that the programme positively impacted on young people in terms of their Sense of Relatedness to others, Sense of Mastery, Social and Emotional Competence and Optimistic Thinking. Furthermore, these findings were not contingent upon the type of loss experienced (bereaved/non-bereaved). Some methodological limitations are highlighted and directions for future research considered.